Application of ISAK 35 concerning the Presentation of Financial Statements of Non-Profit Oriented Entities (Case Study at the Al - Marhamah Orphanage Medan) - Jevri Ansari; Hendra Harmain; Nurwani Nurwani (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to apply the concept of ISAK 35 concerning the Presentation of Financial Statements of Non-Profit Oriented Entities at the Al – Marhamah Orphanage in Medan. The concept of ISAK 35 is to allow non-profit-oriented entities to adjust the descriptions used for some of the posts contained in the financial statements and the financial statements themselves include statements of financial position, comprehensive income statements, reports of changes in net assets, statements of cash flows, and notes to financial statements. At the Al-Marhamah Orphanage in Medan, it has not yet implemented or made financial statements in accordance with this concept, so researchers apply the financial statements. The purpose of this study is to find out how the presentation of financial statements at the Al - Marhamah Medan Orphanage in accordance with the concept of ISAK 35 and to find out the benefits of financial statements that have used ISAK 35 for the Al - Marhamah Medan Orphanage. The data types used are primary data and secondary data. Data collection techniques are carried out using interview and documentation techniques. The data analysis method used is descriptive qualitative. The results of this study are the form of financial statements at the Al - Marhamah Medan Orphanage in 2020 has been adjusted to the concept of ISAK 35, which consists of a Comprehensive Income Report, Cash Flow Statement, Net Asset Change Report, Financial Position Report and Notes to Financial Statements, improving the quality of their financial statements, which later serves as an easier for aid providers to read how the financial statements are and to complete the elements Financial statements and making it easier to find out the surplus (deficit) of orphanage assets in the current year, besides being important, are also very helpful for the following years